Blaming nature, erasing structural accountability: how Indonesian media framed the 2025-Sumatran floods - Oktavian, Winfrey; Dharta, Firdaus Yuni; Susanto, Tri (Jurnal Studi Komunikasi, 2026)
This study examined how major Indonesian online media framed the causes, responsibility, and governance of the 2025 Sumatra flood disaster. Using qualitative content analysis based on Entman’s (1993) problem definition, causal diagnosis, moral evaluation, and treatment recommendation, the study analysed 56 news articles published between 1 and 10 December 2025 from major Indonesian online outlets, including Kompas.com, Tempo.co, Detik.com, CNN Indonesia, CNBC Indonesia, Tribunnews.com, and Liputan6.Com. This study examined the dominant narratives of causation, actor representation, responsibility attribution, and proposed solutions in flood reporting. The findings show that news coverage predominantly framed the floods as extreme weather. At the same time, structural factors such as deforestation, extractive industries, and spatial planning failures appeared less consistently and were often presented as secondary explanations. Government actors were largely represented as responders within a rescue-spectacle narrative, reflecting the political economy of disaster journalism, in which reliance on official sources and state-centred narratives displaces scrutiny of governance failures and extractive interests that produce flood vulnerability. These framing patterns contribute to the normalisation of floods as natural disasters and limit public attention to the need for structural accountability. This study contributes to disaster journalism and environmental communication research by highlighting how media framing shapes the understanding of responsibility for climate-related disasters.